CLINICAL EFFICACY OF CEFTRIAXONE VERSUS CIPROFLOXACIN IN PAEDIATRIC ENTERIC FEVER - Anila Farhat; Asma Shaukat; Tariq Mahmood Khan (Journal of Bahria University Medical and Dental College)
Objective: Determination of the clinical effectiveness of ciprofloxacin versus ceftriaxone in children with enteric fever on the basis of defervescence within 72 hours of commencement of treatment. Duration and Place of Study: This randomized controlled trial study was carried out from 15th May to 15th November 2017 in pediatrics units of Benazir Bhutto Shaheed Teaching Hospital Abbottabad and Jinnah International Hospital Abbottabad. Methodology: 90 children with uncomplicated enteric fever were admitted and divided randomly into two groups, Group A was administered I/V Ceftriaxone 75mg/kg OD and Group B was given I/V Ciprofloxacin 10mg/kg BD for seven days. Response to drug was taken as defervescence within 72 hours while continued fever after 72 hours was taken as no response. The data was analyzed by using SPSS Version 21.00. Results: In our research study 53(58.9%) children were male and 37(41.1%) patients were female. The mean age was 8.43±3.17 years encompassing 4 to 14 years, mean weight of the patients in kg was 29.54±10.8 kg. Efficacy of ceftriaxone group was 93.3% while in ciprofloxacin group 62.2% patients became afebrile in 72 hours. The proportion of achieving defervescence within 72 hours was higher with ceftriaxone than with ciprofloxacin Conclusion: Ceftriaxone is more efficacious in terms of achieving defervescence than ciprofloxacin in children having enteric fever.